CONVECTION-DIFFUSION OF HEAT TRANSFER IN PERFUSED BIOLOGICAL TISSUE - HAZELIA, NELSON (Universiti Malaysia Sarawak (UNIMAS), 2019)
Convection and diffusion to used describe how scalar quantity is being transport in a space. This convection diffusion equation is benefited many fields of engineering, chemistry as well as biology. Since, during oxygen supplies to living tissues through the microcirculation of blood, convection and diffusion play an important role hence, this convection-diffusion equation can apply as a model solution for this study to helps us to describe heat transfer in perfused biological tissue. For this problem of convection diffusion, Green’s function can be used to solve it. Green’s function is used here because it is a powerful tool of mathematical method used in solving some linear inhomogeneous Partial Differential Equations as well as Ordinary Differential Equations. With the properties of Dirac’s function, this Green’s function is derived by spatially development method of separation of variables. Hence, this method considered more efficient than the other known classical methods. As for the discretization to form weak form of Convection-Diffusion, Finite Difference Method of Central Differencing is use. The main reason for this selection is because of the simplicity when implement in our Matlab program.